Estrategias naturales para el manejo del carbón de la espiga (Ustilago maydis) en el cultivo de maíz (Zea mays L.) en el Ecuador - Sánchez Salvatierra, Melanie Jamileth (2024)
The disease known as head smut, caused by the pathogen Ustilago maydis (Persoon) Roussel, can be easily identified in commercial corn cultivation. The objective was to detail the natural strategies for the management of head smut (Ustilago maydis) in the cultivation of corn (Zea mays L.). In the preparation of this document we sought to obtain updated information from scientific literature, online resources and digital repositories. These sources provided diverse perspectives and concepts from various authors, which were crucial to analyzing the research process. This work was carried out as a non-experimental bibliographic research, using methods of synthesis and summary of the information obtained. The conclusions determined that the symptoms present discoloration until they acquire a brown tone. A notable gray to white mycelial development can be seen throughout the spike. The growth usually originates at the base of the ear and progresses in an upward direction. Fungal infection can occur in various regions of the plant, particularly in young, actively growing tissues affecting the grain (cob) of the crop and causing reductions in yield. No natural control strategies have been identified; However, the implementation of practices such as the application of balanced fertilizers is recommended, according to the results of soil analysis. This is because high concentrations of nitrogen in the soil, combined with low levels of phosphorus, increase the risk of incidence of the disease known as smut.